Upright proton therapy for esthesioneuroblastoma: a single-institution experience - Gordon, Konstantin; Gulidov, Igor; Smyk, Daniil; Semenov, Alexey; Golubev, Kirill; Lemaeva, Alyona; Koryakin, Sergey; Jumaniyazova, Enar; Vishnyakova, Polina; Eremina, Irina; Fatkhudinov, Timur; Kaprin, Andrey (Frontiers in Oncology, 2024)
Aim This study presents an analysis (efficacy and toxicity) of outcomes in patients with esthesioneuroblastoma after pencil beam proton therapy with a fixed beamline in the upright position. Background Esthesioneuroblastoma (ENB) is an extremely rare tumor of sinonasal area located in critical proximity to vital structures. Proton therapy (PT) is often considered the optimal radiation treatment for head-and-neck tumors, although of limited availability. Upright PT delivered using fixed pencil beamline and rotating chair is a fairly promising option. Methods This is a single-center experience describing the outcomes of PT in 14 patients with ENB treated between January 2016 and October 2022; half of the cases had a history of previous irradiation. The therapy was applied using a fixed pencil beamline with 6D-chair for positioning. The median dose was 63 GyRBE (total range 48–70 GyRBE; based on 1.1 RBE multiplier for protons) with 2.0 GyRBE per fraction. The mean gross tumor volume was 109.5 cm3 (17.1–257.7 cm3). Patient demography, pathology, treatment parameters and toxicity data were analyzed. Radiation-induced reactions were assessed according to the Common Terminology Criteria for Adverse Events (CTCAE) v 4.0. Results The median follow-up time was 28 months. The 1- and 2-year locoregional control rates constituted 100% and 88.9%, respectively; the median duration of local control was 52 months. The 1- and 2-year progression-free survival (PFS) rates constituted 92.9% and 75.0%, respectively; the median PFS duration was 52 months. The 1- and 2-year overall survival (OS) rates constituted 92.9% and 84.4%, respectively. Two patients died of non-cancer-related causes (coronavirus-induced pneumonia) and 1 patient died of tumor progression. All patients tolerated PT well without any treatment gaps. Serious late toxicity reactions included glaucoma in 1 patient and cataract in 2 patients, in over half a year since irradiation. Conclusion PT with upright design of the unit affords promising outcomes in terms of disease control and toxicity rates in ENB, a sinonasal tumor of complicated localization.